Konstruksi Realitas Kehidupan Kedua Pemain Game Online: Studi pada Para Pemain Game Online dalam Membentuk Realitas dan Komunitas Virtual - Herawati, Erni (Bina Nusantara University, 2014)
Through the development information technologies, online gaming has become a means of communication and interaction between people. They build a virtual social world between them. The problem of this research is how the online game players build they second or secondary lives, particulary how they create second communities, identity, and space in virtual world. This research use qualitative method. The informants are from the online game player aand the data obtained from observation and interview. The results are second lives has a meaning as parallel wolrd that build as a the first world. This live is represents the imagination of the individual fantasy world that provided by online gaming developers.